2021
DOI: 10.1523/jneurosci.1837-20.2021
|View full text |Cite
|
Sign up to set email alerts
|

Impact of GABAA and GABAB Inhibition on Cortical Dynamics and Perturbational Complexity during Synchronous and Desynchronized States

Abstract: Quantitative estimations of spatiotemporal complexity of cortical activity patterns are used in the clinic as a measure of consciousness levels, but the cortical mechanisms involved are not fully understood. We used a version of the Perturbational Complexity Index adapted to multisite recordings from the ferret (either sex) cerebral cortex in vitro (sPCI) to investigate the role of GABAergic inhibition in cortical complexity. We studied two dynamical states: slow-wave activity (synchronous state) and desynchro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
32
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 84 publications
5
32
0
Order By: Relevance
“…This is in agreement with the morphology of cortical neurons, whereby pyramidal neurons have larger projecting axons with respect to the more local and constrained range of inhibitory axons [36][37][38]. This has also been reflected in numerous computational studies [30,[39][40][41][42].…”
Section: Model Synapsessupporting
confidence: 84%
“…This is in agreement with the morphology of cortical neurons, whereby pyramidal neurons have larger projecting axons with respect to the more local and constrained range of inhibitory axons [36][37][38]. This has also been reflected in numerous computational studies [30,[39][40][41][42].…”
Section: Model Synapsessupporting
confidence: 84%
“…For example, in mean field models, GABAergic and glutamatergic synaptic changes are attributed to a single parameter that maps to different concentrations of general anesthesia [27]. Other modelling approaches seek to understand the mechanism of specific anesthetic agents; for example, the effects of propofol have been studied through the modeling of both GABA A and GABA B amplitude/duration and the effects on cortical synchrony and EEG rhythms [18, 28]. Enflurane and isoflurane are other commonly modeled anesthetics where the roles of both glutamatergic receptor binding and GABAergic effects are taken into consideration [2830].…”
Section: Discussionmentioning
confidence: 99%
“…Prior experimental studies demonstrated that the behavioral expression of the anesthetic state can be reversed by stimulating the cholinergic system of the brain by various means in vivo and in vitro in both humans and animals [15,17,18,47]. To date, no modelling study has attempted to simulate the reversal of neuronal effects of anesthesia by modulating the interaction between cholinergic and other synaptic effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, perturbations with transcranial magnetic stimulation (TMS) evoke a chain of recurrent, complex activations in the cortex, as measured by electroencephalography (EEG), in wakefulness but not during NREM sleep [ 19 ]. In subsequent studies the complexity of brain responses to direct cortical stimuli, quantified by the perturbational complexity index (PCI) [ 20 ] was tested across many different conditions in humans [ 20 , 21 , 22 ], rodents [ 23 , 24 ], and cortical slices [ 25 , 26 ]. While these experiments provided fundamental insights on the effects of neuromodulation, anesthetics, and brain lesions on PCI, the role of basic cytoarchitectonics and local connectivity has never been explored.…”
Section: Introductionmentioning
confidence: 99%